Increased serum interleukin-6 level as a predictive biomarker for atrial fibrillation: A systematic review and meta-analysis - Peng Zhou (Revista Portuguesa de Cardiologia (English Edition), 2020)
Background: Atrial fibrillation (AF) is related to a higher risk of thromboembolic events and mortality. Some studies have demonstrated that the inflammatory biomarker interleukin-6 (IL-6) is associated with a higher risk of higher thrombosis in AF patients, but the real effect of IL-6 remains a controversy. Methods: We conducted a systematic review and meta-analysis to investigate the association between IL-6 and thromboembolic events, as well as bleeding events, acute coronary syndrome (ACS) events and all-cause mortality in AF. Results: A total of five studies involving 22 928 patients met our inclusion criteria for the systematic review. The higher level of IL-6 in AF patients is related to long-term thromboembolic events including stroke (RR 1.44, CI 95% 1.09-1.90, p=0.01). IL-6 meant a higher risk of long-term bleeding risk (RR 1.36, CI 95% 1.06-1.74, p=0.02), ACS risk (RR 1.81, CI 95% 1.43-2.30, p<0.001) and all-cause mortality (RR 2.35, CI 95% 2.09-2.65, p<0.001). Conclusion: A higher level of IL-6 may predict a greater number of long-term thromboembolic events and bleeding events, ACS events and mortality in AF patients. Further studies such as the cut-off point of IL-6 need to be conducted in the future. Resumo: Introdução: A fibrilhação auricular (AF) está relacionada com maior risco de eventos tromboembólicos e de mortalidade. Alguns estudos mostraram que o biomarcador inflamatório interleucina-6 (IL-6) estava associado a maior risco trombótico em doentes com AF, mas o efeito real da IL-6 continua controverso. Métodos: Realizámos uma revisão sistemática e meta-análise para investigar a associação de IL-6 com eventos tromboembólicos assim como eventos hemorrágicos, eventos síndrome coronária aguda e mortalidade total na AF. Resultados: Cinco estudos que envolveram 22 928 doentes preencheram os nossos critérios de inclusão para revisão sistemática. Maior nível de IL-6 em doentes com AF relaciona-se com eventos tromboembólicos em longo prazo, incluindo acidente vascular cerebral (RR 1,44, 95% CI 1,09-1,90, P 0,01), risco de ACS (RR 1,81, 95% CI 1,43-2,30, P<0,001) e mortalidade total (RR 2,35, 95% CI 2,09-2,65, P<0,001). Conclusão: Um nível mais elevado de IL-6 pode prever um maior número de eventos tromboembólicos assim como de eventos hemorrágicos, eventos ACS e mortalidade em doentes com AF. Mais estudos sobre o ponto de corte de IL-6 necessitam ser realizados.